The trajectory of adhesion and resistance of the bank workers Union in the corporativist modernity in Brazil (Revista de História Regional, 2008)
This article analyzes the corporativist constitution of the bank workers Union during the first half of century XX and the class representative conflicts between bankers and workers in banks that had preceded the 1964 military-blow. The alterations in the relations between bankers and bank-workers are understood in this research as part of an immense field of forces where workers and capitalist they carry through incited conflicts, and also alliances, in complex relations of dispute, resistance and cooperation that are developed between its diverse fractions of social class. The permanent process of redefinition of the relations between financer and workers in banks, the formation and the influences of the corporativist politics on the identity formation of the workers and their organization into a Union were reserarched. The segmentation of class and the constitution of big metropolitan syndicate machines that conjugate tactics of organization and representation of the multiple interests of the workers integrated to the strategical objectives of the financial corporations, thus contributing to the conflicting amplification of the real subordination of the work in the capital, were observed.